The Effect Of Implementing Ice Breaking Towards Students Motivation In Learning English At Second Grade In SMK Cendana Padang Panjang - Putri Arifani; Loli Safitri (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2023)
This study aims to find the effect of applying ice breaking on motivation to learn English. This research has been conducted at SMK Cendana Padang Panjang because there are still many students who feel learning English is difficult and boring and many students do not focus on the ongoing lesson. The type of research used is experimental research. The researcher used pre experimental research one group pretest and posttest. The population of this study were students of class XI at SMK Cendana Padang Panjang. In this study, the researcher used the total sample as a sampling technique. The data collection instrument used in this study was a closed questionnaire in the form of a linkert scale. To analyze the data from the experimental class and control class, the researcher conducted a normality test using the Lilifors test and homogeneity test using the F test and to test the hypothesis the researcher used the t test and was consulted into the t table with a significant level (α) = 0.05. Based on the results of the last study, the motivation score of students before who were taught by ice breaking was 74,1 and students who was taught by ice breaking was 86,95. There is significant effect of using Ice Breaking to improve students motivation and There is significant difference between students who are taught with the Ice Breaking strategy and those who are taught without Ice breaking.